HUKUM EKONOMI TERKAIT PEMBANGUNAN EKONOMI INDUSTRI PERTAHANAN DI INDONESIA - Tri Susdarwono, Endro (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
Various studies of legal and economic relations show that economic progress will not succees without the development of the law that preceded it. In fact it is said that strengthening legal institutions is “precondition for economic change”, “crucial to the viability of new political systems”, and “an agent of social change. One of the defense industry management devices deemed necessary to encourage the national industry to become more professional, innovative, effective and efficient, integrated in meeting the availability of defense equipment independently, is a regulation number 16 of 2012 concerning the Defense Industry.Key Words: economic law, development, defense industry economic